Case Study: Nursing Implementation of Taking Medication in Patients with Auditory Hallucinations - Saputri, Ayu; Agustin, Ismar (International Journal Scientific and Professional, 2023)
Medication adherence is the level of individual accuracy with medical advice that describes the use of medication according to the instructions and instructions on the prescription, including using it at the correct time. Patients who are not compliant in taking medication tend to experience relapses easily. Frequent relapses in sufferers result in bad effects on the brain which makes it difficult for sufferers to recover. This research aims to obtain an overview of the level of adherence to taking medication and provide knowledge about the importance of taking medication in patients with sensory perception disorders, auditory hallucinations. This case study research is descriptive in nature, with an implementation method using nursing care which was carried out on 8-15 April 2021, the case study subjects were two patients with sensory perception disorders, auditory hallucinations in the Cempaka ward of the Ernaldi Bahar Hospital, South Sumatra Province. After implementing it on patients, the result was that taking medication regularly was very effective in controlling hallucinations because patients were taught to know the five correct principles in taking medication, namely the correct patient, the correct drug, the correct dose, the correct method/route of administration, and the correct time for administering the drug. where compliance occurs if the rules for taking prescribed medication and administering it in the hospital are followed correctly